The Incidence and Risk Factors Associated with Posttraumatic Stress Disorders among Parents of NICU Hospitalized Preterm Neonates - Azam Tofighi Naeem; Mamak Shariat; Mohammad Reza Zarkesh; Nasrin Abedinia; Sara Teimoory bakhsh; Fatemeh Nayeri (Mashhad University of Medical Sciences, 2019)
Background: Parents of preterm neonates are exposed to great stress that can lead to posttraumatic stress disorder. The current study aimed to assess the incidence of posttraumatic stress disorders (PTSD) in both mothers and fathers of preterm infants. Methods: A prospective cohort study was done at two Iranian hospitals in 2016. One hundred and sixty parents of preterm neonates entered the study. A questionnaire related to acute stress disorder (ASD) was completed for parents at days 3-5 after birth. One month later, the parents were asked for the second interview. Prenatal posttraumatic stress questionnaire (PPQ) for mothers and posttraumatic stress disorder checklist (PCL) for fathers were completed. Prevalence of PTSD among the mothers and fathers was compared. Results: According to the results, 32.5% of all mothers and 4% of all fathers showed ASD. After a month, 40% of the mothers and 21.5% of the fathers showed PTSD. A significant correlation was seen between PPQ and PCL scores (P<0.001). There were also significant correlations between both father's and mother's ASD scores with mother's PPQ score (P=0.019, P<0.001). The PPQ scores among employed mothers and mothers with unemployed husbands were significantly higher than others (P=0.038, OR=2.46; P=0.02, OR=0.436). A history of an accident during recent years for mother could change both mother's ASD and PPQ scores (P=0.002, OR=0.133; P=0.002, OR=0.15). Both PPQ and PCL scores also increased by father's history of an accident during recent years (P=0.02, OR=0.541; P=0.01, OR=0.325). Conclusion: The ASD and PTSD among mothers were more frequent than in fathers. Fathers indicated delayed onset of PTSD in comparison with mothers.